Dialectical thinking, gratitude, and positive reframing of the COVID-19 pandemic in Singapore - Tan, Yi Ning Helene (Nanyang Technological University, 2021)
The COVID-19 pandemic generated much stress and uncertainty for people across the world. The present research examines how people cope with such challenging times with a cultural lens by exploring the relationship between cultural thinking styles and coping with the COVID-19 pandemic in the Singapore context. Specifically, it was hypothesised that dialectical thinking would elicit a tendency to positively reframe the pandemic and to be more grateful. To test this, participants were experimentally manipulated to think dialectically through exposure to a text description and an experiential recall task. Positive reframing was measured by looking at how positively or negatively participants viewed self-generated outcomes of the pandemic, while gratitude was measured using an established scale. Results revealed that while all participants were positive, participants primed with dialectical thinking actually viewed the pandemic less positively than participants who were not primed with dialectical thinking. Participants across both conditions did not differ in levels of gratitude. Correlational findings were consistent with past research on dialectical thinking and positive reframing, and identified an additional finding that dialectical thinking has a marginal correlation with gratitude. Possible explanations for inconclusive and unexpected data, limitations of the present study, and future directions are discussed. Keywords: dialectical thinking, coping, positive reframing, gratitude, COVID-19, Singapore